Introducing a Semi-Structural Macroeconomic Model for Rwanda - Charry, Luisa; Gupta, Pranav; Thakoor, Vimal (Washington, D.C. : International Monetary Fund, 2014)
We develop a simple semistructural model for the Rwandan economy to better understand the monetary policy transmission mechanism. A key feature of the model is the introduction of a modified uncovered interest parity condition to capture key structural features of Rwanda's economy and policy framework, such as the limited degree of capital mobility. A filtration of the observed data through the model allows us to illustrate the contribution of various factors to inflation dynamics and its deviations from the inflation target. Our results, consistent with evidence for other countries in the region, suggest that food and oil prices as well as the exchange rate have accounted for the bulk of inflation dynamics in Rwanda.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet